Nordostarktische Fischbestände - Fangempfehlungen für 1998 - Schöne, Rüdiger (1998)
The results of the assessments on North-east fish stocks of cod, haddock, saithe, redfish and Greenland halibut by the ICES ”Arctic Fisheries Working Group” in 1997 are presented. Whereas the stocks of cod, haddock and saithe are considered to be in fairly good conditions and within safe biological limits the assessments show the stocks of beaked redfish and Greenland halibut to be low. Assessments of cod and haddock differed from previous years, because data on cannibalism were introduced into the recruitment models.